Pengaruh Digital Marketing dan Brand Awareness Terhadap Keputusan Pembelian Melalui Mediasi Kepercayaan - Nofriandi Putra; Vicky Brama Kumbara; Della Asmaria Putri (CV. ITTC INDONESIA, 2026)
This study aims to analyze the influence of Digital Marketing and Brand Awareness on Purchase Decision, with Customer Trush as a mediating variabel among Shopee users. The population of this research consists of Management studens at UPI YPTK, class of 2022. A quantitative method with a causal descriptive approch was employed. Data were collected through questionnaires distributed to respondents selected via purposive sampling technique. The data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results of thisstudy are expected to demonstrate the extent to which digital marketing strategies and brand awareness effectiveness build consumer trush to enhance online purchase decision.